CLASS II a class scheduling system for the University of the Philippines College Baguio - Ampongan, Adonis C.; Fabros, Rizal Y.; Magno, Roma G. (2002)
With a fairly large student population which is sure to escalate as the school in transformed into an autonomous unit, the University of the Philippines Baguio's manual class scheduling system is indeed tedious work. A previous automated Class Scheduling System was created in the 1st semester of the school year 2001-2002. Although already a development as compared to the manual process of schedule generation, it could still be much improved in terms of speed and user-friendliness. This project was therefore undertaken with one goal: to optimize CLASS 1, the 1st version of the Class Scheduling System. To achieve this aim, the group propose a system that uses a different scheduling algorithm from that of CLASS(i.e. a combination of the greedy algorithm and iterative improvement algorithm, giving us the tabular sheet method) and subdivides the schedule generation procedure into smaller groups (using graph theories) to somehow speed-up the process. This document is divided into chapters to elucidate on the purpose of the project. Chapter 1 gives an introduction of the problem, and states the objectives and scope of the project. Chapter 2 then discusses theories used as well as reviews previous systems for the solution of the problem. An explanation of the proposed solution is found in Chapter 3. Chapter 4 explains using waterfall paradigm the development and implementations of the system. Chapter 5 presents the results of the system based on the objectives stated in chapter 1. Chapter 6 gives summary of the features of the software, and discusses the conclusions and recommendations made by the group regarding the system that was developed -- Author's abstract.